2020
DOI: 10.1088/1361-6528/ab9bd7
|View full text |Cite
|
Sign up to set email alerts
|

Hot-carrier separation in heterostructure nanowires observed by electron-beam induced current

Abstract: The separation of hot carriers in semiconductors is of interest for applications such as thermovoltaic photodetection and third-generation photovoltaics. Semiconductor nanowires offer several potential advantages for effective hot-carrier separation such as: a high degree of control and flexibility in heterostructure-based band engineering, increased hot-carrier temperatures compared to bulk, and a geometry well suited for local control of light absorption. Indeed, InAs nanowires with a short InP energy barrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 28 publications
4
13
0
Order By: Relevance
“…These observations matches well with the mechanism for photocurrent generation described earlier (Fig. 10(a)) and the carrier separation observed 161 by EBIC in Fig. 10(b).…”
Section: Vc Spatial Control Of Light Absorption In Nanowiressupporting
confidence: 92%
See 2 more Smart Citations
“…These observations matches well with the mechanism for photocurrent generation described earlier (Fig. 10(a)) and the carrier separation observed 161 by EBIC in Fig. 10(b).…”
Section: Vc Spatial Control Of Light Absorption In Nanowiressupporting
confidence: 92%
“…10(c), an effective hot-carrier relaxation length on the order of 100 nm was extracted. 161 Similar numbers have been found with the help of EBIC for holes in InSb/InAs nanowires. 162 Not yet published data of Kumar et al 136 observed ballistic transport of 0.5 eV electrons over a distance on the order of 200-260nm in InAs nanowires.…”
Section: Vb3 Hot-carrier Photovoltaic Energy Conversion In Nanowiressupporting
confidence: 76%
See 1 more Smart Citation
“…Despite the extensive work on the topic, most studies involved only a macroscopic description of the problem, while the fewer existing state-of-the-art modelling of the NESS have several limitations. First, the tenet that the photo-excited HCs ultimately achieve the lattice temperature in the steady-state [31] has been challenged in a recent experiment on group III-V semiconductors; it unveils that in the NESS carrier temperatures can be much higher than lattice temperature [32][33][34][35]. A theoretical understanding of the existence of such a high carrier-temperature in NESS is still lacking [32][33][34][35], especially in light of the different techniques available for measuring the various temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, this possibility of measuring local temperature on the nanoscale was leveraged to image the Peltier effect in graphene nanoconstrictions 3 and nanowire heterostructures. 4 Spatially-resolved images of the Seebeck effect were measured as well by engineering local heaters with scanning tunneling 5 or thermal 3,4 microscopes, focused laser 6 or electron 7 beams, or Joule-heated nanowires. 8 Contrary to conventional (longitudinal) thermoelectric measurements that are performed across two terminals, such experiments involve a third terminal (e.g.…”
mentioning
confidence: 99%